2022
DOI: 10.7759/cureus.23482
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Adult Patients With Idiopathic Pulmonary Hemosiderosis and Lane-Hamilton Syndrome: A Systematic Review of the Literature in the Period 1971-2022

Abstract: Idiopathic pulmonary hemosiderosis (IPH) causes diffuse alveolar hemorrhage (DAH) by a yet unknown mechanism. The coexistence of IPH and celiac disease (CD), also known as Lane-Hamilton syndrome (LHS), has been reported in both pediatric and adult patients. The objective of this study was to compare demographics, clinical and radiologic findings, treatment, and outcomes between adult patients with IPH and LHS. This is a systematic review of the literature. Multiple databases were searched using appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(32 citation statements)
references
References 101 publications
0
32
0
Order By: Relevance
“…Patients diagnosed with IPH should routinely undergo serologic testing for CD at the time of diagnosis regardless of GI symptoms. The risk of recurrence and death in patients with LHS showed a lower trend than patients without CD (the difference did not reach statistical significance) 42 …”
Section: Clinical Aspects In Iphmentioning
confidence: 83%
See 3 more Smart Citations
“…Patients diagnosed with IPH should routinely undergo serologic testing for CD at the time of diagnosis regardless of GI symptoms. The risk of recurrence and death in patients with LHS showed a lower trend than patients without CD (the difference did not reach statistical significance) 42 …”
Section: Clinical Aspects In Iphmentioning
confidence: 83%
“…Despite being more common in girls, pediatric patients with LHS demonstrate a slight preference for boys (56.5%) 43 . Nearly 80% of adult patients with LHS were found to be males in one study 42 . However, another review reported a higher incidence of LHS in adult women 44 .…”
Section: Clinical Aspects In Iphmentioning
confidence: 95%
See 2 more Smart Citations
“…We have recently discussed the prevalence of autoantibodies in a cohort of adult IPH patients as reported in the literature [ 13 ]. Similar to pediatric patients, a majority of these patients had antibodies suggestive of celiac disease (CD), a combination known as Lane Hamilton syndrome (LHS) [ 12 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%